Pelatihan Strategi Pemasaran sebagai Upaya Meningkatkan Penjualan UMKM - Rika Sarfika; Mulyanti Roberto Muliantino; Luciana Luthan; Febi Sagitaria (Warta Pengabdian Andalas, 2022)
Micro, Small and Medium Enterprises (MSMEs) are essential in economic development. The higher the MSMEs' income, the more the country's economy will increase. The ability to do marketing is needed to attract consumers, increase sales, maintain good relations with consumers, to advance MSMEs' income. However, due to limited knowledge, many MSMEs still need to be constrained by marketing, as experienced by Healthy Snacks "Umi Wiwik". This activity aimed to provide marketing strategy training to increase partners' knowledge and ability to market their products. The partners for this activity were members of the MSMEs of Umi Wiwik in the Ampiang Parak District, totalling seven people. The training started with brainstorming, lecturing, and practice methods. Pre-test and post-test measurements were carried out to determine the difference in the participants' knowledge before and after the training. Participants' knowledge data was processed and analyzed using a paired T-test. The results of the activity showed that there was a significant difference in knowledge between the pre-test and post-test (p-value = 0.0001 [p<α]) with a score difference of 1.143. Partners were also able to practice marketing through Instagram and Facebook social media. Based on these results, it can be concluded that this training has increased partners' knowledge and skills in conducting marketing. The team will work on a follow-up to evaluate the sustainability of the activity and its impact on sales and evaluate the obstacles and challenges partners face.